The Presence of Portuguese and Indonesia in Timor Leste as Depicted by Australian and British Broadcasting Corporation: CDA Perspective (Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
The discussion in this paper is intended to describe how Australian Broadcasting Corporation (ABC) and British Broadcasting Corporation (BBC) views Timor Leste during the period of Portuguese occupation, Indonesia’s presence, until the present-day conditions. Using some van Dijk’s models of CDA to examine the statements to represent its history in some editorials published by ABC and BBC news resources, the analysis was carried out at the levels of selected statements with regard to the linguistic features of lexical choices, nominalization, passivization, and overcompleteness. The results of the analysis show that the statements constructed by ABC and BBC’s news editorials as the news discourse about the history of Timor Leste in such relations are discursively biased in terms of CDA. With various differences in terms of the linguistic features, the result also in line with the view that both ABC and BBC’s statements are mostly dichotomizing Portuguese into ‘Us’ while Indonesia into ‘Them’ in terms of van Dijk’s ‘ideological square’.